Modeling of salt water intrusions into Langat River Estuary, Malaysia - Abd Aris, Norhabina (2012)
This study used one-dimensional model approach to determine salt water intrusion of Langat River. The objective of the study is to produce a methodology for rapid assessment of the impact water abstraction on the saline intrusion in the Langat River. The first step is to produce a simple model of saline intrusion in estuaries and evaluate the impact of water abstraction from river, based on resulting salinity intrusion model. The sampling measurement has been taken during intermediate, neap and spring tide at high and low water. These observation was then applied the one dimensional saline intrusion model which has been proposed by Ippen and Harleman (1961) to predict future saline intrusion length using best fit line analysis. The study found that saline water intruded further to the upstream up to 28.29 km during spring tide at high water compare to 13.85 km during intermediate at low water. The river water stratification layer has been determined using Ippen and Harleman (1961) approach. The study revealed that the Langat River behavior ranged from partially-mixed to well-mixed estuary. There are different values of diffusion coefficients, Do for every tide conditions which ranged from 495 to 3219. Hydrological analysis such as return period and 7-days low flow also has been carried out in this study. From this study, one dimensional model has predicted saline will intrude further upstream up to 55 km with instantaneous salinity distribution, s/so=0.20 on year 2020. This model was suitable to predict saline intrusion length during intermediate tide using best fit line analysis. This study found that the amount water left in the river for year 2020 will be less than year 2004 due to higher water demand with 259% increase in population. Rise of water abstraction from the river may affect to saline water intrude to further to the upstream and affect the quality of drinking water. Therefore the rate of salt water intrusion should also be taken into account in decision-making, particularly for water resource of water supply.